Carbon–polymer composites with extreme electrical conductivity. Issue 30 (28th April 2015) - Planes, Emilie; Gloaguen, Francois; Flandin, Lionel
ABSTRACT The aim of this study was to develop Carbon–polymer composites with extreme electrical conductivity (100 S/cm) combined with good flexural strength. Despite the many optimization methods described in the literature, no comprehensive optimization procedure was to be found because the formulation did not control by itself the final properties. This study showed the major influence of the processing conditions with these peculiar materials. A detailed study of the influence of the processing conditions on the microstructural and macroscopic properties was performed. We, thereby, proposed a comprehensive way to optimize the properties of the final product. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42274.